2014
DOI: 10.3109/07420528.2014.957306
|View full text |Cite
|
Sign up to set email alerts
|

The impact of training schedules on the sleep and fatigue of elite athletes

Abstract: In any sport, successful performance requires a planned approach to training and recovery. While sleep is recognized as an essential component of this approach, the amount and quality of sleep routinely obtained by elite athletes has not been systematically evaluated. Data were collected from 70 nationally ranked athletes from seven different sports. Athletes wore wrist activity monitors and completed self-report sleep/training diaries for 2 weeks during normal training. The athletes also recorded their fatigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
180
4
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(213 citation statements)
references
References 39 publications
(50 reference statements)
15
180
4
14
Order By: Relevance
“…No difference in TST prior to training versus rest days was observed in rugby league players when training commenced at 07:3068 or 09:00 30. Shifting training start from 06:30 to 09:30 increased prior TST in judo athletes,13 while a study that examined the effect of different training start times found athletes who started between 05:00 and 06:00 obtained less than 5 hours of TST, and those who started between 10:00 and 11:00 obtained more than 7 hours 63. It was predicted that TST will reduce by just 6 min when start is advanced from 08:00 to 07:00, but by 48 min when advanced from 08:00 to 06:00 63.…”
Section: Resultsmentioning
confidence: 98%
“…No difference in TST prior to training versus rest days was observed in rugby league players when training commenced at 07:3068 or 09:00 30. Shifting training start from 06:30 to 09:30 increased prior TST in judo athletes,13 while a study that examined the effect of different training start times found athletes who started between 05:00 and 06:00 obtained less than 5 hours of TST, and those who started between 10:00 and 11:00 obtained more than 7 hours 63. It was predicted that TST will reduce by just 6 min when start is advanced from 08:00 to 07:00, but by 48 min when advanced from 08:00 to 06:00 63.…”
Section: Resultsmentioning
confidence: 98%
“…Sleep loss appears to be prevalent among athletes and might result in an alarming issue (Sargent, Lastella, et al, 2014). Concerning sleep deprivation, significant effects on psychomotor performance have been reported (Reilly & Edwards, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, research informs of a worldwide prevalence of inadequate sleep among adolescents due to the combination of biological changes and societal demands 94. Coaches of adolescent-athletes should be aware that delayed sleep and wake routines among youth athletes increase basal sleep requirements which cannot be assuaged because of training or schooling schedules in the morning 95 96. The consequences of chronic sleep loss may be greater on youth athlete due to their increased sleep requirements.…”
Section: Other Considerations In Talent Identification and Developmentmentioning
confidence: 99%